The efficiency and effectiveness of leadership in operational management level in organization - Seita, Almandeel; Waheeb, Abu-Ulbeh; Ahmed Hassan, Hassan; Yousef A.Baker, El-Ebiary; Samer, Bamansoor; Syarilla Iryani, A. Saany (2020)
Nowadays, the topic of Operational Management System in the operational level of organization are still widely discussed. This review paper aims to analyse the efficiency and effectiveness of Operational Management System in organization. The usage of Transaction processing systems (TPS) in operational management system is an information processing system for business transactions involving collection, modification and retrieval of all transaction data. TPS include in performance, Leadership, reliability and consistency which will be very much help in smoothing the organization’s work. The methodology used in this paper is to collect, analyse and evaluate papers. Moreover, the top popular issues consist of the Impact of strategic operational management, Impact of Operational Management Proficiency and Approach to staff behaviour in operational management perspective respectively. This study emphasized the impact of Operational Management in organizations as a topic for the growing of organizations in requiring operational management capabilities.